2017
DOI: 10.1038/srep42710
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid alterations identified in chronic hepatitis B, hepatitis B virus-associated cirrhosis and carcinoma patients

Abstract: The incidences of chronic hepatitis B (CHB), Hepatitis B virus (HBV)-associated cirrhosis and HBV-associated carcinoma are high and increasing. This study was designed to evaluate serum lipid metabolite changes that are associated with the progression from CHB to HBV-associated cirrhosis and ultimately to HBV-associated HCC. A targeted metabolomic assay was performed in fasting sera from 136 CHB patients, 104 HBV-associated cirrhosis, and 95 HBV-associated HCC using ultra-performance liquid chromatography trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 69 publications
1
38
0
Order By: Relevance
“…In this large sample of Chinese LTRs, the incidence of NODAT in the first postoperative year increased to 30.3%, which is consistent with the findings of previous reports . The preoperative lipid profile of our study population was characterized by prevalent hypocholesterolemia and hypotriglyceridemia, and similar findings were reported by studies of patients with HBV‐associated cirrhosis or carcinoma, which are the two leading causes of liver transplantation . In the present study, discordant associations between preoperative lipid indices and incident NODAT were observed.…”
Section: Discussionsupporting
confidence: 92%
“…In this large sample of Chinese LTRs, the incidence of NODAT in the first postoperative year increased to 30.3%, which is consistent with the findings of previous reports . The preoperative lipid profile of our study population was characterized by prevalent hypocholesterolemia and hypotriglyceridemia, and similar findings were reported by studies of patients with HBV‐associated cirrhosis or carcinoma, which are the two leading causes of liver transplantation . In the present study, discordant associations between preoperative lipid indices and incident NODAT were observed.…”
Section: Discussionsupporting
confidence: 92%
“…The sensitivity and specificity of AFP, a tumor marker widely used in the clinic, are not notably high [ 23 ], and most patients are already in an advanced stage. Researchers have been looking for new blood markers of HCC, such as AFP-L3, DCP and SCCA [ 24 ], and have evaluated serum metabolism during the progression from CHB to HCC [ 10 , 11 ], but they have not been widely used. In this study, we found that the panel of L-serine, creatine and glycine distinguished LC from CHB, and L-serine, cystathionine, creatine and linoleic acid distinguished HCC from LC and NC, indicating that the panels of multiple DMs may be beneficial to distinguish CHB, LC, and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the serum metabolic profiles in the progression of HBV infection to HCC using a non-targeted gas chromatography-time of flight-mass spectrometry (GC-TOFMS), and 15 metabolites were determined to be intimately associated with the process [ 10 ]. Wu T et al evaluated the dynamic change in serum lipid metabolism during the progression from CHB to HCC by targeted metabolomics analysis and concluded that the serum levels of long-chain lysophosphatidylcholines (lysoPCs) were promising markers of HBV-associated carcinoma [ 11 ]. In addition, most of the related studies on HCC metabolism have focused on glucose metabolism [ 12 , 13 ] and fatty acids metabolism [ 14 ], and relatively little is known about other metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The HCV-RNA circulates in large spherical particles, which bind in a competitive way with LDL and VLDL [20] and inhibition of microsomal triglyceride transfer protein by HCV infection leads to reduced VLDL secretion by hepatocytes, ultimately leading to decreased serum concentrations of VLDL and LDL [21]. In HBV, on the other hand, serum lipid levels are not affected [22], leading to higher absolute serum cholesterol levels than in HCV. Based on the findings in this large patient cohort, further research on the association between dyslipidemia, steatosis and CLD of different etiologies is warranted.…”
Section: Discussionmentioning
confidence: 99%